MECHANISM OF Ni(II) UPTAKE STUDIES BY EPR, FTIR AND XRF: BIOSORPTION CHARACTERISTICS IN BATCH AND DYNAMIC FLOW MODE - Dundar, Murat; Nuhoglu, Yasar; Nuhoglu, Cigdem (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2015)
The present study aimed Ni(II) ion biosorption from synthetic wastewaters with the another pollutant matter (waste pomace of Rose damascena, WPORD) which are abundant, rather inexpensive and high metal binding capacity. Batch sorption kinetic experiments were performed in order to investigate adsorbent and adsorbat dose, solution pH, agitating speed and temperature. Adsorption equilibrium was reached within 60 min. The maximum Ni(II) adsorption was obtained at pH 4.0. The equilibrium data fit well the Langmuir isotherm. The monolayer adsorption capacities of WPORD at 60 degrees C was found to be 22.37 mg g(-1). The adsorption mechanism was examined by the FTIR, SEM, EPR and XRF techniques. The EPR and activation energy studies shows that Ni(II) adsorption on WPORD is of a physical nature and diffusion-controlled processes. The applicability of sorbent system was investigated in a continuous mode. Column studies were performed under different biosorbent dosage. The proposed sorbent system in dynamic flow-treatment mode was successfully used to remove the nickel ions from wastewater
Keywords: Ni(II) biosorption; waste pomace of Rose damascena; batch and column studies; AQUEOUS-SOLUTION; WASTE-WATER; NICKEL(II) IONS; ADSORPTION; REMOVAL; COPPER(II); CU(II); CHROMIUM(VI); LEAD(II); LITTER; Environmental Sciences & Ecology